Antioxidant Activity, Total Phenolic and Flavonoid Contents of Three Onobrychis Species from Iran - Roya Karamian , Mostafa Asadbegy (Tabriz University of Medical Sciences, 2016)
Background: Plant phenolic compounds are a main group of plant natural products and flavonoids are the largest and best studied natural phenols. These substances possess a series of biological properties and act on biological systems as antioxidants. In present research, the aim is to determine in vitro total phenolics content and antioxidant activity of the methanolic extracts of three Onobrychis species belonging to the family Fabaceae, namely O. sosnovskyi Grossh., O. viciifolia Scop. and O. melanotricha Boiss. Furthermore, an attempt was made to identify any correlations between total phenolic content of the extracts with their antioxidant activities Methods: Total phenol and flavonoid contents of the extracts were determined by Folin-Ciocalteu and aluminum chloride methods, respectively. Antioxidant activity was evaluated by three different test systems, namely 2, 2-diphenyl-1-picrylhydrazyl free radical scavenging (DPPH), metal-chelation activity and ß-carotene/linoleic acid model. Results: Results indicated that O. viciifolia extract contains the highest total phenolic content (10.38 ± 0.33mg GAE/g of dry extract). However, the species are not remarkable different (P < 0.05) in total flavonoid amount. The Onobrychis species represent strong antioxidant activity in DPPH radical scavenging (IC50; 0.121 ± 0.005 to 0.129 ± 0.001 mg/ml), metal chelating (IC50; 1.10 ± 0.006 to 1.80 ± 0.003 mg/ml) and also β-carotene bleaching methods. In addition, a high correlation was found between different antioxidant assays and total phenol content of the extracts (R2 > 0.55 to 0.98). Conclusion: Our results showed that the examined Onobrychis extracts represent strong antioxidant activity; hence, they can be suggested as antioxidant agents for special use in future.